Sports Science & Weightlifting for teens - Alexopoulos, Dimitris; Salpas, Vasilis (Open Schools Journal for Open Science, 2024)
In this project we delve into weightlifting and its principals, while mostly emphasizing on the safety of teenage lifters. Nevertheless, the bigger realm where weightlifting belongs, sport science, is also analyzed quite extensively, covering most related professions and branches. Apart from showcasing some examples of weightlifting activity, its benefits for every age group are highlighted. The main controversial topic researched, though, is whether teenagers’ growth is going to be stunned due to the external loads that need to be moved. By including detailed but essential studies, doctors’ and experts’ opinions, we manage to map out the parameters that are to be taken into consideration. The physical prowess achieved from such exercise is then correlated with renowned psychologists’ theories concerning character and ethical development of physically capable persons.